LÁSZLÓ KÜRTI & PETER SKALNÍK (eds.): Postsocialist Europe. An- thropological Perspectives from Home. Oxford: Berghahn 2009. 336 sider. ISBN 978-1-84545-474-6. Pris: £ 50. - Borch, Signe (Tidsskriftet Antropologi, 2011)
Intet resumé